Beneficial Cardiac Structural and Functional Adaptations After Lumbosacral Spinal Cord Epidural Stimulation and Task-Specific Interventions: A Pilot Study - Legg Ditterline, Bonnie E.; Wade, Shelley; Ugiliweneza, Beatrice; Singam, Narayana Sarma; Harkema, Susan J.; Stoddard, Marcus F.; Hirsch, Glenn A. (Frontiers in Neuroscience, 2020)
Cardiac myocyte atrophy and resulting decreases to left ventricular mass and dimensions are well-documented in spinal cord injury. Therapeutic interventions that increase preload can increase chamber size and improve diastolic filling ratios, however, there are no data describing cardiac adaptation to chronic afterload increases. Research from our center has demonstrated spinal cord epidural stimulation can normalize arterial blood pressure, so we decided to investigate the effects of spinal cord epidural stimulation on cardiac function using echocardiography. Four individuals with chronic, motor-complete cervical spinal cord injury were implanted with a stimulator over the lumbosacral enlargement. We assessed cardiac structure and function at the following timepoints: a) prior to implantation; b) after spinal cord epidural stimulation targeted to increase systolic blood pressure; c) after addition of spinal cord epidural stimulation targeted to facilitate voluntary (i.e., with intent) movement of the trunk and lower extremities; d) and after addition of spinal cord epidural stimulation targeted to facilitate independent, overground standing. We found significant improvements to cardiac structure (left ventricular mass: 10 ± 2 g, p < .001; internal dimension during diastole: 0.1 ± 0.04 cm, p < .05; internal dimension during systole: 0.06 ± 0.03 cm, p < .05; interventricular septum dimension: 0.04 ± 0.02 cm, p < .05), systolic function (ejection fraction: 1 ± 0.4 %, p < .05; velocity time integral: 2 ± 0.4 cm, p < .001; stroke volume (4.4 ± 1.5 mL, p < .01), and diastolic function (mitral valve deceleration time: -32 ± 11 ms, p < .05; mitral valve deceleration slope: 50 ± 25 cm*s-1, p < .05; isovolumic relaxation time: -6 ± 1.9 ms, p < .05) with each subsequent scES intervention. Despite the pilot nature of this study statistically significant improvements to cardiac structure, systolic function, and diastolic function demonstrate spinal cord epidural stimulation combined with task-specific interventions led to beneficial cardiac remodeling which can reverse atrophic changes that result from spinal cord injury. Long-term improvements to cardiac function have implications for increased quality of life and improved cardiovascular health in individuals with spinal cord injury, decreasing risk for cardiovascular morbidity and mortality.